Corporate Restructuring in Thailand after the 1997 Financial Crisis: Evidence from Corporate Governance Reform - Sudchai, Angsumalin (2006)
Thailand experienced a down turn in the economy during the financial crisis in 1997. The fundamental element was that at the time companies in Thailand had raised large amounts of money by borrowing to invest in projects that turned out to generate insufficient income to pay back their debts. These circumstances almost automatically led to the crisis because these highly leveraged companies were not only unable to make repayments, but their lenders' own financial standing also deteriorated.